Picturing the Party: Instagram and Party Campaigning in the 2014 Swedish Elections. (August 2016) - Filimonov, Kirill; Russmann, Uta; Svensson, Jakob
This article explores Swedish parties' activities on Instagram during the 2014 elections. Understanding party campaign communication as highly strategic, that is, communication to persuade and mobilize voters in order to win the elections, we ask whether Instagram was used to (1) broadcast campaign messages, (2) mobilize supporters, (3) manage the party's image, and (4) amplify and complement other campaign material (i.e., hybrid campaign use). With this study, we follow previous studies on the use of digital communication platforms in the hands of campaigning political actors, but we direct our attention to a new platform. We conducted a content analysis of 220 party postings on Instagram, collected during the hot phase of the campaign. The result shows that the platform was mainly used for broadcasting rather than for mobilization. The image the parties were presenting leaned toward personalization with a strong presence of top candidates in their postings. Top candidates were primarily displayed in a political/professional context. Finally, half of the analyzed postings showed signs of hybridized campaign practices. The presented findings give a first glimpse on how political parties use and perform on Instagram.